UMPSA research recognised with 3 gold and 3 silver medals at ITEX 2025 - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 30 May 2025 – Six research projects from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were recognised after winning three gold and three silver medals at this year’s International Invention, Innovation & Technology Exhibition (ITEX) 2025.